Community Participation in Qanun Formulation in Gayo Lues Regency - Umar*, Ali; Bakar, Muhammad Abu; Wulandari, Florentina Ratih (Universitas Syiah Kuala, 2024)
https://jurnal.usk.ac.id/riwayatCommunity participation is a public administration perspective, in the formulation of qanun it is a form of public policy at the regional level which includes the regulation of various aspects of local life with all the benefits needed in the process of administering government. The aim of this research is to analysed and determine strategies for community participation in the formulation of qanun in Gayo Lues Regency. The research method used in this research is a qualitative approach. Primary data in this research was obtained directly through interviews about the research theme. Data collection techniques were carried out using Library Research (library research) and Field Research (field research). Data analysis uses qualitative analysis which is presented and explained in the discussion. The results of this research are that the process of formulating qanuns should not be carried out by one party alone, but requires the involvement of all parties both within the state structure and outside the state structure as a form of community participation in the development process. Participating in the formulation of qanuns is a community right that can be exercised both in the preparation and discussion stages, so that every community member needs their presence, both physical and conceptual, to provide substantial input into each qanun that is formed. Strategies to increase community participation in the formulation of qanuns in Gayo Lues Regency and what forms of participation the community can take in the process of forming qanuns. Several conclusions can be made, including, Qanun is the highest policy at the regional level, therefore community and stakeholder participation is absolutely necessary to ensure that the qanun is in Favor of the community, as well as guaranteeing the possibility of the qanun being enforced. A policy is needed to increase public participation in the formation of qanuns, namely, the government must provide education about the step by step process of forming qanuns, and there needs to be a clear and firm mechanism regarding the urgency of the intended participation. Forms of participation that can be carried out by the community include, taking part in public hearings either in the council building or going directly to the location of the relevant community or through seminars or workshops, attending trials at the DPRK building, conducting opinion polls, contacting the public through the mass media.